High Incidence of Hippocampal Abnormalities in Pediatric Patients with Congenital Cytomegalovirus Infection - Natsume, Takenori; Inaba, Yuji; Osawa, Yoshihiro; Fukuyama, Tetsuhiro (Neuropediatrics, 2022)
Background Congenital cytomegalovirus (CMV) infection exhibits polymicrogyria, intracranial calcification, white matter lesions, and several types of intracranial lesions on magnetic resonance imaging (MRI), in addition to various developmental disorders and epilepsies. However, little is known on the presence of hippocampal abnormality in this affliction. The aim of this study is to clarify the incidence of hippocampal abnormality in congenital CMV infection.Methods Seventeen children diagnosed as having congenital CMV infection along with 17 age-matched pediatric controls were retrospectively evaluated by brain MRI and clinical review. The measurement data were obtained from conventional coronal sections in this retrospective study. Hippocampal malrotation (HIMAL) was defined as a hippocampal diameter ratio (i.e., the ratio of the height and width of the hippocampus) of >0.92.Results Hippocampal diameter ratios were significantly higher in the congenital CMV infection group (0.99 [range: 0.70–1.58] on the right side and 0.85 [range: 0.66–1.39] on the left side) than in controls (0.71 [range: 0.58–0.91] and 0.70 [range: 0.50–1.00], respectively). HIMAL was present in 17 of 34 hippocampi (50%) in the congenital CMV infection group and 1 of 34 hippocampi (2.9%) in controls. No correlations were detected between HIMAL and intelligence quotient/developmental quotient or the occurrences of autism spectrum disorder or epilepsy.Conclusion This study is the first to demonstrate the incidence of hippocampal abnormality to be significantly higher in congenital CMV infection patients than in age-matched controls. Further study is necessary to clarify the associations of HIMAL with other clinical and developmental features.
Keywords: brain magnetic resonance imaging; congenital cytomegalovirus infection; hippocampal malrotation; hippocampus